Gel transition of depletion flocculated emulsions - Berli, Claudio Luis Alberto (2003)
The gel transition of depletion flocculated oil-in-water emulsions is analyzed as a function of the strength of the droplet–droplet interaction. The critical volume fraction for gelation has been found to decrease exponentially with the magnitude of the interaction energy at contact, in agreement with recent proposals for aggregating colloids. The viscosity modeling of these emulsions had been discussed in a previous work (Colloids Surf. A 203 (2002) 11). The results reported here show the interplay between phase behavior and rheology of flocculated emulsions.